2010
DOI: 10.1007/s11099-010-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics of diploid honeysuckle (Lonicera japonica Thunb.) and its autotetraploid cultivar subjected to elevated ozone exposure

Abstract: In order to investigate the effect of chromosome doubling on ozone tolerance, we compared the physiological responses of a diploid honeysuckle (Lonicera japonica Thunb.) and its autotetraploid cultivar to elevated ozone (O 3 ) exposure (70 ng g -1 , 7 h d -1 for 31 d). Net photosynthetic rate (P N ) of both cultivars were drastically (P<0.01) impaired by O 3 . Although there were significantly positive correlation between P N and stomatal conductance (g s ) in both cultivars under each treatment, the decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The reductions in photosynthesis are typically driven by both a reduction in leaf chlorophyll content (Heagle et al 1996;Sharma et al 2003) and the quantity and activity of the primary carboxylation enzyme Rubisco (Fiscus et al 2005;Ojanpera et al 1998). Further, whole-plant fumigation experiments suggest that decreases in photosynthesis can be independent of stomatal conductance (Francini et al 2007;Noormets et al 2001;Zhang et al 2010), suggesting that decreases in carboxylation, rather than conductance, are responsible for decreases in light-saturated photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The reductions in photosynthesis are typically driven by both a reduction in leaf chlorophyll content (Heagle et al 1996;Sharma et al 2003) and the quantity and activity of the primary carboxylation enzyme Rubisco (Fiscus et al 2005;Ojanpera et al 1998). Further, whole-plant fumigation experiments suggest that decreases in photosynthesis can be independent of stomatal conductance (Francini et al 2007;Noormets et al 2001;Zhang et al 2010), suggesting that decreases in carboxylation, rather than conductance, are responsible for decreases in light-saturated photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…CE indicates carbon assimilation (Ding et al, 2014), and its decrease under yeast treatment was probably due to the reduction in activity and/or quantity of Rubisco (Zhang et al, 2010). P n decreased after 6 days of yeast treatment, while CE showed no decrease, indicating that yeast did not impair mesophyll processes (Zhang et al, 2010). Therefore, the decrease in P n was caused by stomatal factors under yeast treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in the efficiency of photosynthetic electron transport between diploid and tetraploid plants grown in non-stressed conditions documented in the literature are usually small and non-significant (e.g. [ 20 , 37 , 38 , 40 , 81 ]. However, Majdi et al [ 76 ] demonstrated significantly lower values of maximum photochemical efficiency of photosystem II in tetraploid Tanacetum parthenium compared to diploid individuals.…”
Section: Discussionmentioning
confidence: 99%